Increased densities of monocarboxylate transporter MCT1 after chronic hyperglycemia in rat brain - Canis, Martin; Maurer, Martin H.; Kuschinsky, Wolfgang; Duembgen, Lutz; Duelli, Roman (Brain research, 2009)
The brain is capable of taking up monocarboxylates as energy substrates. Under physiological conditions, plasma levels of monocarboxylates are very low and glucose is the primary energy substrate in brain metabolism. However, given conditions such as hyperglycemia and ketosis, levels of circulating monocarboxylates such as lactate and pyruvate are elevated. Previous studies reported an increased expression of monocarboxylate transporter MCT1 in brain following ketotic diet. The major aim of the present study was to answer the question whether chronic hyperglycemia is likewise sufficient to change local densities of MCT1 in the brain. Moreover, chronic hyperglycemia increases local cerebral glucose utilization (LCGU) in particular brain areas. Glucose hereby enters the brain parenchyma via glucose transporters and is partially metabolised by astrocytes, which then release lactate to meet the energetic demands of surrounding neurons. Streptozotocin was given intravenously to induce chronic hyperglycemia and local densities of MCT1 were measured by immunoautoradiographic methods in cryosections of rat brains. The density of monocarboxylate transporter MCT1 was significantly increased in 10 of 24 brain structures investigated (median increase 11.7±3.4 %). Immunocytochemical stainings of these substructures revealed an expression of MCT1 within endothelial cells and astrocytes. A comparison of MCT1 densities with LCGU measured in a previous study under normo- and hyperglycemic conditions revealed a partial correlation between both parameters and under both conditions. Four out of 10 brain areas, which showed a significant increase in MCT1 density due to hyperglycemia, also showed a significant increase in LCGU. In summary, our data show that chronic hyperglycemia induces a moderate increase of local and global density of MCT1 in several brain structures. However, in terms of brain topologies and substructures this phenomenon did only partially match with increased LCGU. It is concluded that MCT1 transporters were up-regulated during chronic hyperglycemia at the level of brain substructures and independently of LCGU.
Available online 11 December 2008
Gesehen am 27.04.2021